PENGEMBANGAN DESAIN SUVENIR UNTUK KAMPUNG WISATA SAYURAN KTD GEMAH RIPAH BAUSASRAN - Pandapotan, Dan Daniel Pandapotan; Catarina Aprilia Ariestanti; Koniherawati (Servirisma, 2024)
Souvenirs are one of the strategic products needed by KTD Gemah Ripah. Souvenirs were given to representatives of the group as a symbol and proof of friendship between institutions. Currently, KTD Gemah Ripah needs new souvenirs that can increase the meaning of tourism activities. The aim of the service is to develop community potential through creating new bowl-shaped souvenir designs. The service method is divided into several stages, namely observation, interviews and workshops. The output is a souvenir bowl. The results of the service are applied to serve Brazilian spinach noodles which are processed themselves by KTD Gemah Ripah. The KTD Gemah Ripah community was actively involved in carrying out the design process by filling in the modules. Sketches from the module are translated into finished products for testing. Based on this service activity, KTD Gemah Ripah was satisfied with the souvenir designs they produced. They gain valuable experience because they have knowledge of the design process. At the end of this activity, the author saw the potential of KTD Gemah Ripah in utilizing the surrounding environment as a reference for developing new souvenirs. The novelty of the souvenir can be seen in the variety of motifs produced by each workshop participant.